1992
DOI: 10.1088/0953-4075/25/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple electron capture by highly charged ions at keV energies

Abstract: The status of the knowledge on the mechanisms of multiple captures by a highly charged ion colliding with an atom is reviewed. The various and complementary techniques are first described, including energy gain spectroscopy, electron and photon spectroscopy with a particular emphasis on the rapidly developing techniques combining these spectroscopies in coincidence experiments. The double capture processes are simple enough to allow theoretical calculations and a detailed analysis of capture mechanisms such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
69
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(76 citation statements)
references
References 107 publications
3
69
0
4
Order By: Relevance
“…In parallel, theoretical methods, such as the classical overbarrier (COB) model [8], the Landau-Zener model [9], the classical trajectory Monte Carlo (CTMC) model [10], and molecular expansion close-coupling methods [11] have been developed. From such experimental and theoretical works, the main features have been explained successfully over a wide range of impact velocities [1,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, theoretical methods, such as the classical overbarrier (COB) model [8], the Landau-Zener model [9], the classical trajectory Monte Carlo (CTMC) model [10], and molecular expansion close-coupling methods [11] have been developed. From such experimental and theoretical works, the main features have been explained successfully over a wide range of impact velocities [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, even in the case of collisions involving only two active electrons, the processes responsible for DEC are still under debate [12,[18][19][20][21]. While DEC can be rather well described using independent electron models, it has been shown that dynamic correlation effects due to the electronelectron interaction which is not incorporated in these models may play a decisive role during the collision [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…But at heat-scale collision energies, two-electron processes with rearrangement [3]- [7] become equally probable or even sometimes prevail over one-electron processes. These two-electron processes include various Auger processes [7], the two-electron charge exchange processes [3]- [6], and the charge exchange with simultaneous ion excitation [4]. Because the total cross sections and rate constants of these processes are large, we can assume that these processes with rearrangement are governed by electron transitions at relatively large distances R between colliding particles.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the small parameter 1/R allows developing a consistent asymptotic theory of the process under investigation. This is why several "memorable" results in the theory of multielectron atom-ion processes with rearrangement were obtained in the framework of the asymptotic approach [3], [4], [6]. * Uzhgorod National University, Uzhgorod, Ukraine, e-mail: lazur@univ.uzhgorod.ua, o.pavlik75@mail.ru, reiti@univ.uzhgorod.ua.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation